Management of Pediatric Skin-Graft Donor Sites. Issue 1 (January 2015) - Brenner, Maria; Hilliard, Carol; Peel, Glynis; Crispino, Gloria; Geraghty, Ruth; O'Callaghan, Gill
<x xml:space="preserve">Abstract</x> Skin grafts are used to treat many types of skin defects in children, including burns, traumatic wounds, and revision of scars. The objective of this prospective randomized controlled trial was to compare the effectiveness of three dressing types for pediatric donor sites: foam, hydrofiber, and calcium alginate. Children attending a pediatric Burns & Plastics Service from October 2010 to March 2013, who required a split-skin graft, were recruited to the trial. Patients were randomly assigned to the two experimental groups, foam or hydrofiber, and to the control group, calcium alginate. Data were gathered on the management of exudate, assessment of pain, time to healing, and infection. Fifty-seven children aged 1 to 16 years (mean = 4.9 years) were recruited to the trial. Fifty-six patients had evaluable data and one participant from the control group was lost to follow-up. Most children required skin grafting for a burn injury (78%). The median size of the donor site was 63.50 cm2 (8–600 cm2). There was a statistically significant difference in time to healing across the three dressing groups (x2 [2, n = 56] = 6.59, P = .037). The calcium alginate group recorded a lower median value of days to healing (median = 7.5 days) compared to the other two groups, which recorded median values of 8 days (hydrofiber) and 9.5 days (foam). The greatest leakage of exudate, regardless of dressing type, occurred on day 2 after grafting. No statistically significant difference was found in leakage of exudate, pain scores, or infection rates across the three groups. Calcium alginate emerged as the optimum dressing for pediatric donor site healing in this trial.